Nonlinear dynamic analysis of low viscosity fluid-lubricated tilting-pad journal bearing for different design parameters - Yingze Jin; Fei Chen; Jimin Xu; Xiaoyang Yuan (Friction)
Abstract To reveal nonlinear dynamic rules of low viscosity fluid-lubricated tilting-pad journal bearings (TPJBs), the effects of design parameters on journal center orbits and dynamic minimum film thicknesses of water-lubricated TPJBs with and without static loads are investigated. The hydrodynamic bearing force used in the nonlinear dynamic analysis is an approximate analytical solution including the turbulence effect. The results reveal the methods for vibration suppression and load capacity improvement and give an optimal pivot offset and clearance ratio that can maximize the minimum film thickness. The results also show that four-pad TPJBs with loads between pads are preferred due to good dynamic performance and load capacity. This study would provide some guidance for nonlinear design of low viscosity fluid-lubricated TPJBs under dynamic loads.